The Influence of Extrusion Geometry and Ratio on Extrudate Mechanical Properties for a 6005A Alloy Containing Either Sc and Zr or Cr and Mn Dispersoid Formers - Eli Harma; Paul Sanders; Thomas Wood; Timothy Langan (Journal of Manufacturing and Materials Processing)
There is a demand for a 6005A series extrusion alloy with improved strength that maintains good extrudability. Replacing Mn and Cr dispersoid formers with Sc and Zr is expected to increase the room temperature mechanical properties while not affecting extrudability. Al3X dispersoids with a Sc core surrounded by a Zr shell are stable at higher temperatures and enhance recrystallization resistance and precipitation strengthening. However, there is little information on how the Sc and Zr additions affect the properties of an extrudate as a function of extrusion geometry and ratio. A 6005A series alloy with Cr and Mn additions is compared to an alloy with Sc and Zr additions with rod and flat cross-sections at extrusion ratios of 25 and 92. The results show that Sc and Zr additions increased yield strength and ultimate tensile strength while maintaining ductility compared to Cr and Mn additions. Rod shapes performed significantly better than flat shapes, but there was no significant effect of extrusion ratio.